Effect of Cryoapplication on Fractal Organization of Ultrastructure of Parodontium Soft Tissues in Destruction and Penumbra Zones - Marchenko, V. S.; Marchenko, L. N.; Yermakova, N. Yu.; Sleta, I. V.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2009)
With the methods of electron, optical, laser microscopy in combination with computer morphometry there has been proved morphological informativeness of fractal dimensions to estimate a general state of the tissue of oral cavity. It has been shown that the application of dosed cryoeffect leads to the strengthening of transcytosis, increase in lability, fractalization of ultra-thin elements of hematosalivary barrier.